Molla Mustafa Barzani in the USA 1975–1979 - Özoğlu, Hakan (The Copernicus Journal of Political Studies, 2018)
The article presents the result of a research on the final years of Mulla Mustafa Barzani on the basis of US intelligence reports concluded in the late 1970s and declassified in 2006, as well as memoirs and articles by U.S. foreign officers. The author focuses on the documents prepared by the CIA in relation with the travel of Barzani to the U.S. for medical treatment. The selected material concerns issues such as: U.S. support for the last Kurdish uprising headed by Mustafa Barzani and its nature, Barzani’s request from the U.S. after the Algiers Accord of 1975, behind-the-curtain negotiations regarding Barzani’s travel to the U.S., and the restrictions imposed on him during his stay. The author also considers the possibilities connected with the phrase “requested asylum” used for Barzani’s application to travel to the U.S.: from misinformation on the part of CIA officer, actually seeking refuge, to a political move aimed at enlisting U.S. support for the Kurdish cause. The author encourages the readers to form their own opinions on the presented matter. However, one indisputable fact remains – the U.S. has always been very much interested in Kurdish nationalism and the Kurds were a significant subject in the Cold War years. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14760